Ibrutinib-Associated Life-Threatening Hemorrhage with Subcapsular Renal Hematoma and Hemothorax - Gaudel, Pramod; Brubaker, Autumn; Huang, Caitlyn; Verkruyse, Linda; Huang, Chao (Archives of Clinical and Medical Case Reports, 2022)
Background: Ibrutinib is an irreversible inhibitor of Bruton tyrosine kinase (BTK) which is FDA approved for treatment of chronic lymphocytic leukemia (CLL) and multiple other B-cell lymphoproliferative disorders. Ibrutinib therapy is associated with increased risk of bleeding. We report an unusual but life-threatening case of hemorrhage with subcapsular renal hematoma and large hemothorax secondary to Ibrutinib. Case Presentation: An 85-year-old male with history of CLL started on a reduced dose of ibrutinib presented with acute onset left sided flank pain and dyspnea. He was found to have bicytopenia with acute anemia, thrombocytopenia, and acute kidney failure. Imaging revealed moderate to large left sided pleural effusion and a renal mass concerning for renal neoplasm. He underwent thoracentesis revealing hemothorax. The patient was managed conservatively with intravenous hydration for his acute renal failure, blood transfusions and pain medications. His pain resolved; blood counts eventually stabilized and he was discharged from the hospital. The renal mass was later diagnosed as a large subcapsular renal hematoma after further review by another radiologist who determined that the Hounsfield unit of the mass was consistent with blood. Conclusions: This case illustrates a case of life-threatening hemorrhage that required hospitalization after 2 weeks of initiation of ibrutinib. Hemorrhage can occur despite reduced dose, and can result in hemorrhagic pleural effusion and bleeding in solid organs like the kidney. The presence of sudden large masses in a solid organ in a patient on ibrutinib should elicit the differential of intra-organ hemorrhage. Initiation of ibrutinib should be done cautiously, especially in elderly patients.